2000
DOI: 10.1126/science.289.5482.1197
|View full text |Cite
|
Sign up to set email alerts
|

Genes Expressed in Human Tumor Endothelium

Abstract: To gain a molecular understanding of tumor angiogenesis, we compared gene expression patterns of endothelial cells derived from blood vessels of normal and malignant colorectal tissues. Of over 170 transcripts predominantly expressed in the endothelium, 79 were differentially expressed, including 46 that were specifically elevated in tumor-associated endothelium. Several of these genes encode extracellular matrix proteins, but most are of unknown function. Most of these tumor endothelial markers were expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
1,207
4
9

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,679 publications
(1,254 citation statements)
references
References 34 publications
34
1,207
4
9
Order By: Relevance
“…Moreover, by applying siRNA technology, we were able to demonstrate that signals emanated by IL-3 binding to its receptors are crucial for TEC proliferation and migration in vitro and for in vivo vessel formation as well. Blood vessels supplying tumors are considered unique as they differ from their normal counterparts with respect to morphology, pathophysiology, gene expression profile and outgrowth in the absence of growth factors (St Croix et al, 2000;Baluk et al, 2003). Considerable evidences have currently emerged sustaining the key role of Akt in driving TEC proangiogenic phenotype (Bussolati et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by applying siRNA technology, we were able to demonstrate that signals emanated by IL-3 binding to its receptors are crucial for TEC proliferation and migration in vitro and for in vivo vessel formation as well. Blood vessels supplying tumors are considered unique as they differ from their normal counterparts with respect to morphology, pathophysiology, gene expression profile and outgrowth in the absence of growth factors (St Croix et al, 2000;Baluk et al, 2003). Considerable evidences have currently emerged sustaining the key role of Akt in driving TEC proangiogenic phenotype (Bussolati et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike NECs in normal quiescent endothelium, TECs have a rapid turnover rate and therefore have been termed 'activated'. The 'activated' phenotype of TECs (Folkman, 2007) has been related to the expression of embryonic genes (St Croix et al, 2000) as well as genes regulating vessel growth, including the interleukin (IL)-3 gene (Bussolati et al, 2003). The inflammatory cytokine IL-3, released into tumor microenvironment (Dentelli et al, 2004), besides promoting survival and proliferation of mature endothelial cells (Dentelli et al, 1999), also acts as an endothelial differentiation factor for hematopoieticderived endothelial progenitor cells (EPCs) (Zeoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of 12 genes increased at least twofold and the expression of 26 genes decreased at least twofold when ID4 was elevated (Supplementary Table S1). We systematically searched the literature for information about each of these genes, but the expression patterns and documented biologies associated with these genes did not suggest a function in angiogenesis, except in the case of matrix GLA protein (MGP) (St Croix et al, 2000;Bostrom et al, 2004).…”
Section: Identification Of a Potential Id4 Target Promoting Angiogenementioning
confidence: 99%
“…In 2000, St. Croix et al found that the mRNA most upregulated in a sample of human colon cancer vascular cells was the message for endosialin (TEM1) 6061. Later, endosialin was found to be expressed in the vasculature and fibroblasts of human brain tumor specimens, including astrocytoma, anaplastic astrocytoma, glioblastoma multiforme, meningioma, oligodendroglioma, ependymoma and carcinoma brain metastasis 6263.…”
Section: Sarcoma Targetsmentioning
confidence: 99%